Afoxolaner and fluralaner treatment do not impact on cutaneous Demodex populations of healthy dogs. Issue 5 (23rd May 2017) - Zewe, Christine M.; Altet, Laura; Lam, Andrea T. H.; Ferrer, Lluís
Abstract : Background: Fluralaner and afoxolaner are isoxazolines licensed for the treatment of flea and tick infestations. Isoxazolines have also shown efficacy for treatment of demodicosis. Nothing is known about the impact of these compounds on the populations of Demodex in healthy dogs. Hypothesis/Objectives: The objective of this study was to measure the prevalence of Demodex in the skin of healthy dogs prior to and following the use of either afoxolaner or fluralaner, using real‐time PCR (RT‐PCR) for Demodex DNA. Our hypothesis was that the use of an isoxazoline at the labelled dose would eliminate Demodex populations from the skin of healthy dogs. Animals and methods: Twenty healthy dogs with no history of skin disease were recruited. Dogs were divided into two groups of ten, with each group receiving afoxolaner or fluralaner for the 90 day study period. Hairs were plucked from three body sites on Day 0 prior to medication administration, then again on days 30 and 90. RT‐PCR amplifying Demodex DNA was performed on all samples. Results: At Day 0 (prior to treatment), five of the 20 dogs were positive for Demodex DNA at least in one skin site (25%). At Day 60, three of 18 dogs were positive (16.7%) and on Day 90, six of 20 dogs were positive (30%). No significant difference in numbers of positive dogs was found between groups or timepoints. Conclusion: Treatment with afoxolaner or fluralaner does not impact on cutaneous Demodex populations of normal dogs over a 90 day period. Abstract : Background – Fluralaner and afoxolaner are isoxazolines licensed for the treatment of flea and tick infestations. Isoxazolines have also shown efficacy for treatment of demodicosis. Nothing is known about the impact of these compounds on the populations of Demodex in healthy dogs.Hypothesis/Objectives – The objective of this study was to measure the prevalence of Demodex in the skin of healthy dogs prior to and following the use of either afoxolaner or fluralaner, using real‐time PCR for Demodex DNA. Our hypothesis was that the use of an isoxazoline at the labelled dose would eliminate Demodex populations from the skin of healthy dogs.Conclusion – Treatment with afoxolaner or fluralaner does not impact on cutaneous Demodex populations of normal dogs over a 90 day period.